Embodied Recovery: Phenomenological Reflections on Sensory Human Rights in Asian Drug Rehabilitation Spaces (Lembaga Contrarius Indonesia, 2026)
Drug rehabilitation in Asia remains dominated by coercive approaches that often disregard the human body as a central medium of healing. This paper introduces the concept of Embodied Recovery, grounded in Merleau-Ponty’s phenomenology of embodiment and Ibn Sīnā’s model of sensory and cognitive perception, to examine the sensory and bodily dimensions of rehabilitation. Using a desk review approach, this study aims (1) to identify the characteristics and implications of coercive rehabilitation practices across Asia; (2) to analyze the relationship between bodily sensory experience and the recovery process; and (3) to assess the application of human rights–based rehabilitation within the Maqasid al-Shariah framework. Findings reveal that neglecting sensory and embodied experiences weakens cognitive and moral restoration, as the senses serve as the primary gateway to reason (‘aql). When the body’s sensory engagement is suppressed, rehabilitation risks perpetuating psychological distress and spiritual disconnection. The study concludes that integrating phenomenological and Islamic perspectives offers a more ethical, human-centered model of recovery one that recognizes sensory awareness as fundamental to holistic well-being and human dignity in accordance with Maqasid al-Shariah.